Heart and neural crest derivative 2‐induced preservation of sympathetic neurons attenuates sarcopenia with aging. Issue 1 (30th November 2020) - Rodrigues, Anna Carolina Zaia; Wang, Zhong‐Min; Messi, María Laura; Bonilla, Henry Jacob; Liu, Liang; Freeman, Willard M.; Delbono, Osvaldo
Abstract: Background: Sarcopenia, or age‐dependent decline in muscle force and power, impairs mobility, increasing the risk of falls, institutionalization, co‐morbidity, and premature death. The discovery of adrenoceptors, which mediate the effects of the sympathetic nervous system (SNS) neurotransmitter norepinephrine on specific tissues, sparked the development of sympathomimetics that have profound influence on skeletal muscle mass. However, chronic administration has serious side effects that preclude their use for muscle‐wasting conditions. Interventions that can adjust neurotransmitter release to changing physiological demands depend on understanding how the SNS affects neuromuscular transmission, muscle motor innervation, and muscle mass. Methods: We examined age‐dependent expression of the heart and neural crest derivative 2 (Hand2), a critical transcription factor for SN maintenance, and we tested the possibility that inducing its expression exclusively in sympathetic neurons (SN) will prevent (i) motor denervation, (ii) impaired neuromuscular junction (NMJ) transmission, and (iii) loss of muscle mass and function in old mice. To test this hypothesis, we delivered a viral vector carrying Hand2 expression or an empty vector exclusively in SNs by vein injection in 16‐month‐old C57BL/6 mice that were sacrificed 6 months later. Techniques include RNA‐sequencing, real‐time PCR, genomic DNA methylation, viral vector construct, tissue immunohistochemistry, immunoblot, confocal microscopy, electrophysiology, and in vivo mouse physical performance. Results: Hand2 expression declines throughout life, but inducing its expression increased (i) the number and size of SNs, (ii) muscle sympathetic innervation, (iii) muscle weight and force and whole‐body strength, (iv) myofiber size but not muscle fibre‐type composition, (v) NMJ transmission and nerve‐evoked muscle force, and (vi) motor innervation in old mice. Additionally, the SN controls a set of genes to reduce inflammation and to promote transcription factor activity, cell signalling, and synapse in the skeletal muscle. Hand2 DNA methylation may contribute, at least partially, to gene silencing. Conclusions: Selective expression of Hand2 in the mouse SNs from middle age through old age increases muscle mass and force by (i) regulating skeletal muscle sympathetic and motor innervation; (ii) improving acetylcholine receptor stability and NMJ transmission; (iii) preventing inflammation and myofibrillar protein degradation; (iv) increasing autophagy; and (v) probably enhancing protein synthesis.